The field guide to understanding 'human error' - Dekker, Sidney (Farnham, Surrey, England Burlington, VT, USA Ashgate, 2014)
"This latest edition of The Field Guide to Understanding 'Human Error ' will help you understand how to move beyond 'human error'; how to understand accidents; how to do better investigations; how to understand and improve your safety work. You will be invited to think creatively and differently about the safety issues you and your organization face. In each, you will find possibilities for a new language, for different concepts, and for new leverage points to influence your own thinking and practice, as well as that of your colleagues and organization"--Provided by publisher.
Includes bibliographical references and index.
Keywords: System failures (Engineering); Human engineering; Industrial accidents